The Implementation, Policy Sanctions for No-Smoking Area at Pertamina Bintang Amin Hospital Lampung Bandar Lampung - Priyogo, Adib; Samino, Samino; Yulyani, Vera; Muhammad, Muhammad (Universitas Aisyah Pringsewu, 2022)
Cigarette consumption in Indonesia, especially in Lampung Province and Bandar Lampung City is still high. Policies in the form of laws, provincial regulations and Bandar Lampung City regulations regarding non-smoking areas (NSA) aimed at suppressing the growth rate of cigarette users have not shown success. Pertamina Bintang Amin Hospital Lampung (PBAH) is an area that is required to implement the NSA policy, but visitors are still found smoking. The aim is to determine the implementation of the no-smoking area policy in the hospital. The study utilized a qualitative research method with a case study approach. The data collection was through in-depth interviews, document reviews, and field observations. Nine informants were selected purposively. Data analysis used a thematic analysis approach. The results of the data analysis obtained information that the PBAH had implemented the NSA policy with the decision of the director of the hospital and as the supervisory team. The policy foundations of the hospital are the Health Law, Provincial Local Regulation and Bandar Lampung City Local Regulation. The monitoring process in the building has been going well, as evidenced by the absence of employees/visitors smoking, but outside the building, especially in the parking area, it has not been maximized, this is because the area is quite large and cannot be reached by the supervisor. Sanctions for hospitals that do not implement the NSA policy can be subject to administrative sanctions in the form of a warning. They can be up to the revocation of operational permits. More severe sanctions can be in the form of fines or corporal punishment. It can be concluded that the implementation of the NSA policy at the PBAH has generally been going well. It is recommended that additional NSA signs in the parking area and an expansion of the number of supervisors are needed.Abstrak: Konsumsi rokok di Indonesia, khusunya Provinsi Lampung maupun Kota Bandarlampung masih tinggi. Kebijakan berupa UU, Perda Provinsi maupun Perda Kota Bandarlampung mengenai kawasan tanpa rokok (KTR) bertujuan untuk menekan laju pertumbuhan pengguna rokok belum menunjukkan keberhasilannya. Rumah Sakit Pertamina Bintang Amin Lampung (RSPBA) termasuk kawasan wajib menerapkan kebijakan KTR, namun masih ditemukan pengunjung merokok. Tujuan untuk mengetahui implementasi kebijakan kawasan tanpa rokok di RS tersebut. Metode penelitian kualitatif dengan pendekatan studi kasus. Pengumpulan data melalui wawancara mendalam, kajian dokumen, serta observasi lapangan. Informan sembilan orang, dipilih secara purposif. Analisis data menggunakan pendekatan analisis tematik. Hasil analisis data diperoleh informasi RSPBA telah menerapkan kebijakan KTR dengan keputusan direktur dan tim pengawasnya. Landasan kebijakan RS adalah UU Kesehatan, Perda Provinsi dan Perda Kota Bandarlampung. Proses pengawasan dalam gedung telah berjalan dengan baik dibuktikan tidak ada lagi pegawai/pengunjung yang merokok, namun untuk luar gedung khususnya di area perparkiran belum maksimal, hal ini disebabkan kawasannya cukup luas dan tidak terjangkau oleh pengawas. Sanksi RS yang tidak melaksanakan kebijakan KTR dapat dikenakan sanksi administrasi berupa teguran dan dapat sampai pencabutan ijin operasional. Sanksi yang lebih berat dapat berupa pidana denda atau badan. Disimpulkan implementasi kebijakan KTR di RSPBA secara umum telah berjalan dengan baik. Disarankan perlu penambahan rambu-rambu KTR di area perparkiran serta perluasan angkauan pengawas.